CSI, crime scene investigation. The complete seventh season [videorecording (DVD)] - Zuiker, Anthony E., 1968-; Felder, Steven; Fink, Kenneth; Petersen, William L., 1953-; Helgenberger, Marg; Dourdan, Gary; Eads, George, 1967-; Fox, Jorja; Szmanda, Eric; Hall, Robert David; Lombard, Louise, 1970-; Guilfoyle, Paul (CBS DVD : Paramount Home Entertainment, 2007)
An elite team of police forensic evidence investigation experts work their cases in Las Vegas. This season includes Grissom's hunt for the notorious Miniature Killer.